Боротьба з корупційною рентою в Україні: головні етапи та заходи - Губін, К. Г. (ХНУ ім. Ярослава Мудрого, 2019)
Обґрунтовано необхідність задля ефективної протидії корупції зробити наголос на боротьбі з корупційною рентою. Виділено три етапи боротьби з корупційною рентою: зміна структур; забезпечення структур професійними кадрами та створення розвиненої антикорупційної системи. Запропоновано комплекс заходів, необхідних для скорочення можливостей формування корупційної ренти та для ускладнення приховування та використання корупційних доходів. To effectively tackle corruption in Ukraine, it is necessary to emphasize the fight against corruption rent, because without the opportunities to earn and spend corruption rent, the meaning of corruption acts is largely lost. By depriving corrupt officials of their income, we limit their ability to counteract anti-corruption activities. It is often very difficult to expose and prove corruption in court, but it is relatively easy to see the existence of incomes as the result of corruption. The tackling of rent-seeking in Ukraine should be carried out in three stages. The first stage – changing structures – involves the destruction of old corruption institutions, organizations, groups, schemes, etc. and the creation of new institutions, organizations and mechanisms that are immune to corruption and fighting it. This requires people with high moral and ethical qualities who are really committed to effective anticorruption reforms implementation. The second stage is to provide the structures with professional staff. When recruiting employees, it will be possible to shift the emphasis to the professional qualities of applicants, because now the structures themselves will limit the rent-seeking and the attraction to corruption activities. The third stage is the creation of advanced anti-corruption system. Some of the anticorruption measures that are on the verge of violating the rights and freedoms of citizens will have to be abandoned. Corruption fighters will gain considerable experience and will be able to investigate and bring to justice and conviction the most complex and thoroughly concealed corruption offenses. Conclusions. The optimal model for tackling corruption in Ukraine is in limiting the possibilities of formation, accumulation, concealment and use of corruption rent and involves three stages of this task.
Fighting against corruption rent in Ukraine: main stages and activities
Keywords: доходи; реформи в Україні; корупційна рента; боротьба з корупцією; боротьба з корупційною рентою; income; reforms in Ukraine; corruption rent; fight against corruption; fight against corruption rent